Cu-based oxygen carriers for chemical looping processes: opportunities and challenges - Liu, Guicai (2023)
Oxygen carrier (OC) material acting as the intermediate between reactors is key in a chemical looping process. Cu-based OCs are attractive candidates due to the superiority in reactivity, kinetics and capacity during the redox reactions with fuels. The ability of gaseous O2 release and the exothermic property for OC-fuel reaction provide more opportunities in chemical looping applications. This review illustrates the basic properties of Cu-based OCs and the opportunities in several chemical looping processes, including chemical looping combustion (CLC), chemical looping oxygen uncoupling (CLOU), chemical looping air separation (CLAS), chemical looping for syngas/H2 production, integrated CaO/CuO looping process and thermochemical energy storage (TCES). Besides, the technical challenges and the current strategies are discussed on agglomeration, attrition and ash accumulation. A perspective on the future research and development of Cu-based OCs is further discussed. This brief review may help with a better understanding and development for Cu-based OC design and the relevant chemical looping processes.